2002
DOI: 10.1038/sj.jim.7000270
|View full text |Cite
|
Sign up to set email alerts
|

Amylase hyperproduction by deregulated mutants of the thermophilic fungus Thermomyces lanuginosus

Abstract: Thermomyces lanuginosus was subjected to three cycles of mutagenesis (UV/NTG) and a selection procedure to develop amylase-hyperproducing, catabolite-repression-resistant and partially constitutive strains. One of the selected derepressed mutant strain III(51), produced approximately 7- and 3-fold higher specific activity of alpha-amylase (190 U/mg protein) and glucoamylase (105 U/mg protein), respectively, compared to a wild-type parental strain. Further, the effect of production parameters on mutant strain I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…(2) where, X 1 -pH, X 2 -temperature in 0 C and X 3 -inoculum size in %. The larger the magnitudes of F-value, the smaller the pvalue, the more significant value is the corresponding coefficient (Akhnazarova and Kafarov, 1982;Rubinder et al, 2002). The results of the second order response surface model fitting in the form of analysis of variance (ANOVA) are in Table. 6.…”
Section: Resultsmentioning
confidence: 99%
“…(2) where, X 1 -pH, X 2 -temperature in 0 C and X 3 -inoculum size in %. The larger the magnitudes of F-value, the smaller the pvalue, the more significant value is the corresponding coefficient (Akhnazarova and Kafarov, 1982;Rubinder et al, 2002). The results of the second order response surface model fitting in the form of analysis of variance (ANOVA) are in Table. 6.…”
Section: Resultsmentioning
confidence: 99%
“…Phutela et al (2005) reported an optimum temperature of 60°C for thermophilus A. fumigatus pectinase. Other thermophilic fungi have been reported to optimally produce enzymes at 50°C (Rubinder et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Using semi-quantitative plate assay approach, a thermophilic fungal strain TF3 (Aspergillus fumigatus MTCC 4163) isolated from decomposing orange peel waste, was selected as the best producer of pectinase and PG. The plate assay approach has been previously employed in our lab for isolating hyper amylase producing mutants/fusants of thermophilic fungus Thermomyces lanuginosus (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The potency index of each isolate was calculated as the ratio of zone diameter to colony diameter. The cultures showing high potency index were further screened by semiquantitative plate assay method (22,23). The cultures were individually plated on YPSS medium (9) containing pectin in place of starch and incubated at 50ºC.…”
Section: Screening Of Thermophilic Fungal Isolates For Pectinolytic Amentioning
confidence: 99%